Mobility and efficacy of abamectin and imidacloprid against Rhynchophorus ferrugineus in Phoenix canariensis by different application methods - Dembilio, Óscar; Riba, Josep M.; Gamón Vila, Miguel; Jaques, Josep A. (2017)
BACKGROUNDRhynchophorus ferrugineus is the most destructive pest of palms. As detection of early infestation stages is difficult, preventive measures, mostly chemical control, are crucial. Stipe injection of insecticides has developed rapidly as a suitable technique. However, pesticide movement within palms and palm reaction to wounding remain controversial. We used abamectin and imidacloprid applied by crown spray, stipe and frond injections to disentangle how these pesticides move within P. canariensis and how tissues wounded by injection heal. Furthermore, we established their lethal doses to larvae of R. ferrugineus. RESULTSMaximum residues of imidacloprid (0.1mgkg(-1)) were detected in crown and frond samples for up to 2 months after stipe injection, whereas maximum residues of abamectin were found in frond tip samples (0.5mg active substance kg(-1)) 5 months after stipe injection. Based on the lethal concentrations calculated, these doses could satisfactorily protect palms for up to 3 months after treatment. No significant wound damage was observed 2 years after injection. CONCLUSIONStipe injection, irrespective of the active substance considered, resulted in better distribution and higher persistence compared with frond injection and, especially, crown spray. As a consequence, our results point to stipe injection as a good alternative to control R. ferrugineus. (c) 2014 Society of Chemical Industry